The Father-Daughter Relationship in Claudia Piñeiro’s Novel of Formation, Un comunista en calzoncillos - Carolina Rocha (Studies in 20th & 21st Century Literature, 2025)
Un comunista en calzoncillos (2013) is a novel by Claudia Piñeiro that does not belong to the crime genre. This autobiographical text that mainly centers on the writer when she was an adolescent is quite distinct within Piñeiro’s work. In two previous studies of this text, I have examined both the adolescent as an enigmatic child—and the female gender roles available to her—and the figure of the father, touching on his manliness and his performance of a non-hegemonic masculinity in a patriarchal society. I build on these pieces to analyze the father-daughter relationship in Un comunista en calzoncillos. The purpose of this article is two-fold. First, drawing on insights from psychoanalysis, I explore the father-daughter relationship in Piñeiro’s novel. In the second part, I suggest that this text is a novel of formation. It is my contention that the author’s relationship with her father constitutes a vital aspect of her formation as a future writer.
Keywords: Claudia Piñeiro; novel of formation; Un comunista en cazoncillos; father-daughter